Power Estimation and Optimization Methodologies for VLIW-based Embedded Systems - Zaccaria, Vittorio; Sami, M.G.; Sciuto, Donatella; Silvano, Cristina (New York, NY Springer US, 2003)
LOW power design is playing an important role in today ultra-large scale integration (ULSI) design, particularly as we continue to double the number of transistors on a die every two years and increase the frequency of operation at fairly the same rate. Certainly, an important aspect of low power faces with mobile communications and it has a huge impact on our lives, as we are at the start-line of the proliferation of mobile PDA’s (Personal Digital Assistants), Wireless LAN and portable multi-media computing. All of these devices are shaping the way we will be interacting with our family, peers and workplace, thus requiring also a new and innovative low power design paradigm. Furthermore, low power design techniques are becoming paramount in high performance desktop, base-station and server applications, such as high-speed microprocessors, where excess in power dissipation can lead to a number of cooling, reliability and signal integrity concerns severely burdening the total industrialcost. Hence, low power design can be easily anticipated to further come into prominence as we move to next generation System-on-Chip and Network-on-Chip designs. This book is entirely devoted to disseminate the results of a long term research program between Politecnico di Milano (Italy) and STMic- electronics, in the field of architectural exploration and optimization techniques to designing low power embedded systems
Power Estimation Methods -- Background -- Instruction-Level Power Estimation for VLIW Processor Cores -- Software Power Estimation of the LX Core: A Case Study -- System-Level Power Estimation for the LX Architecture -- Microprocessor Abstraction Levels -- Power Optimization Methods -- Background -- A Micro-Architectural Optimization for Low Power -- A Design Space Exploration Methodology -- Conclusions and future work
Keywords: Electronics and Microelectronics, Instrumentation; Computer-Aided Engineering (CAD, CAE) and Design; Computer simulation; Electrical and Electronic Engineering; Electrical engineering; Computer Modelling; Computer networks; Computer Engineering and Networks; Electronic circuits; Computer-aided engineering; Computer engineering; Electronics; Electronic Circuits and Systems